A model for syn-eruptive groundwater flow during the phreatoplinian phase of the 28-29 March 1875 Askja volcano eruption, Iceland - Lupi, M; Geiger, S; Rebecca Carey; Thordarson, T; Houghton, BF (2011)
We present a groundwater flow model that integrates geological observations, field data, effective permeabilities for fractured lava flows, and historical eyewitness records to explain the change from wet to dry explosive activity that occurred in March 1875 at Askja volcano, Iceland. This rhyodacite eruption is the third largest silicic explosive event in Iceland since settlement in this region (approximately 1140 B.P.). It was part of a larger volcano-tectonic episode that took place in the North Volcanic Zone from 1874 to 1876. This eruption is unique in that it features both abrupt and gradual shifts between wet and dry explosive activities. It consisted of an initial and sudden shift from dry subplinian to wet phreatoplinian activity followed by a gradual shift from wet phreatoplinian to increasingly dry pyroclastic density currents to a final dry Plinian phase. The Askja caldera overlaps the Öskjuvatn caldera and it is bounded by steep-sided hyaloclastic mountains on all sides. Its floor is filled by Holocene and historical lava flows which are intensely fractured. The source of water that fuelled the phreatoplinian activity is not obvious, as eyewitness records rule out snow, surface water, and heavy rainfall. Hence we use 3D numerical simulations of the syn-eruptive groundwater flow in the Askja caldera, including an accurate estimation of the effective permeabilities of fractured lava flows, to explain the possible changes in eruptive style. We propose that the water necessary to maintain the phreatoplinian phase was stored within the lava pile and that the rapid groundwater flow through the fractured lavas provided enough water to drive the hour-long phreatoplinian eruption. Our model describes how the decline of the groundwater table caused the progressive dry-out of the wet phase and led to the dry character of the following Plinian activity. This study demonstrates how the availability of groundwater and the geology of the volcanic edifice can strongly affect the eruptive style of a volcanic ...